Pengaruh Penggunaan QRIS, Kemudahan Transaksi, dan Volume Transaksi Terhadap Peningkatan Penjualan Umkm di Surabaya - Fanny Ananda Pratiwi; Muslimin (Yayasan Literasi Ilmiah Indonesia, 2026)
Purpose: This study aims to analyze the effect of QRIS usage, transaction convenience, and transaction volume on increasing MSME sales in Surabaya. Method: This study employed a quantitative approach using primary data collected through questionnaires distributed to MSMEs registered as E-PEKEN partners in Surabaya. The population consisted of 3,427 MSMEs registered in the E-PEKEN program as of December 2025. The sampling technique used was purposive sampling with specific criteria, resulting in 126 respondents. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4 software. Finding: The results indicate that QRIS usage, transaction convenience, and transaction volume have a positive and significant effect on increasing MSME sales in Surabaya. QRIS usage was found to have the strongest influence on sales improvement, followed by transaction volume and transaction convenience. The findings suggest that the adoption of digital payment systems contributes to business growth by improving transaction efficiency, customer convenience, and sales performance. Novelty: This study contributes to the existing literature by examining the simultaneous effects of QRIS usage, transaction convenience, and transaction volume on MSME sales improvement within the context of E-PEKEN partner MSMEs in Surabaya. Unlike previous studies that mainly focused on income or financial performance, this research specifically investigates sales improvement as the main outcome of digital payment adoption.